2016
DOI: 10.2147/ppa.s106577
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the quality of life of patients with acute coronary syndrome treated with percutaneous coronary intervention after a 3-year follow-up

Abstract: BackgroundThe aims of this study were to analyze the dynamics of quality of life (QoL) changes after 36 months from the percutaneous coronary intervention (PCI) depending on sex and identify baseline predictors of the follow-up QoL of patients hospitalized for acute coronary syndrome (ACS) and subjected to PCI.Methods and resultsThe study included 137 patients, females (n=67) and males (n=70), with ACS who underwent PCI. The QoL was assessed using the MacNew Heart Disease Health-Related Quality of Life questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
4
12
1
1
Order By: Relevance
“…Like the majority of earlier studies we observed gender differences in both components of HRQoL, however Bogg 21 found that women scored lower only on emotional HRQoL. Also like other studies of longer-term recovery [7][8][9] we found that gender difference in HRQoL were no longer present 1 year after MI.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Like the majority of earlier studies we observed gender differences in both components of HRQoL, however Bogg 21 found that women scored lower only on emotional HRQoL. Also like other studies of longer-term recovery [7][8][9] we found that gender difference in HRQoL were no longer present 1 year after MI.…”
Section: Discussionsupporting
confidence: 84%
“…However, our finding that in women use of beta-blockers at T1 was associated with higher discomfort at T3 is not consistent with other research. Arendarczyk [37] found that use of beta-blockers two years after MI was positively associated with HRQoL, whereas another study found that use of beta-blockers exacerbated functional decline in older nursing homes residents with cognitive impairment [38]. Use of anxiolytics at T1 positively predicted discomfort in both genders at the earlier timepoints,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It related to both components of HRQoL, but many studies indicate that the effect depends on the HRQoL dimension [21]. Also, like other studies of longer-term recovery [6][7][8], the difference in HRQoL was no longer present 1 year after MI.…”
Section: Discussionmentioning
confidence: 81%
“…There is some evidence that after an MI, women report lower HRQoL than their male counterparts. Most of the differences were observed at short-and medium-term follow-up (up to 3 years after MI), and among patients less than 70 years old; after longer periods (2.5 to 10 years after MI) and among older patients (> 70 years) the gender difference disappeared [6][7][8]. This difference in HRQoL is dangerous and disadvantageous for women, as low HRQoL and lack of improvement in HRQoL have been shown to predict a recurrence of cardiovascular events 6 [9] and 13 years post-MI [10].…”
Section: Gender Differences In Hrqolmentioning
confidence: 98%